1996
DOI: 10.1523/jneurosci.16-11-03775.1996
|View full text |Cite
|
Sign up to set email alerts
|

A Primary Acoustic Startle Pathway: Obligatory Role of Cochlear Root Neurons and the Nucleus Reticularis Pontis Caudalis

Abstract: Davis et al. (1982) proposed a primary acoustic startle circuit in rats consisting of the auditory nerve, posteroventral cochlear nucleus, an area near the ventrolateral lemniscus (VLL), nucleus reticularis pontis caudalis (PnC), and spinal motoneurons. Using fiber-sparing lesions, the present study reevaluated these and other structures together with the role of neurons embedded in the auditory nerve [cochlear root neurons (CRNs)], recently hypothesized to be involved in acoustic startle. Small electrolytic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
212
0
3

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 338 publications
(241 citation statements)
references
References 80 publications
10
212
0
3
Order By: Relevance
“…The fast excitatory pathway of the acoustic startle system involves serial connections linking the auditory nerve, cochlear root neurons, PnC, and spinal motor neurons (Lee et al, 1996). We have previously demonstrated that pulse stimulus increased c-Fos expression in the PnC, which was attenuated by a weak prepulse before pulse stimulus in the PPI test (Takahashi et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…The fast excitatory pathway of the acoustic startle system involves serial connections linking the auditory nerve, cochlear root neurons, PnC, and spinal motor neurons (Lee et al, 1996). We have previously demonstrated that pulse stimulus increased c-Fos expression in the PnC, which was attenuated by a weak prepulse before pulse stimulus in the PPI test (Takahashi et al, 2007).…”
Section: Discussionmentioning
confidence: 94%
“…Liang and colleagues (1992) reported that electrolytic lesions of the amygdala blocked CRH-enhanced startle, whereas CRH infused into the amygdala failed to mimic intracerebroventricular CRH effects on startle. Because the amygdala has direct projections to the nucleus reticularis pontis caudalis (Hitchcock and Davis, 1991), a part of the primary acoustic startle circuit (Davis et al, 1982;Lee et al, 1996), these data suggest that the amygdala may play an obligatory role in CRH-enhanced startle, even though it is not the primary receptor site for CRH given intracerebroventricularly. In other words, CRH given intracerebroventricularly may bind to receptors in structures afferent to the amygdala, such as the BNST or hippocampus, thereby exciting the amygdala indirectly.…”
mentioning
confidence: 93%
“…Taken together, these results add to a body of work showing that GABAergic transmission at the level of the deep SC/Me is an important component in the regulation and expression of motor behaviors. Because the deep SC/Me is not part of the primary acoustic startle pathway (Lingenhöhl and Friauf, 1994;Lee et al, 1996), the results of the present study suggest that the deep SC/Me exerts a modulatory influence on this reflex. A recent report from our laboratory has identified a heavy ipsilateral innervation from the deep SC/Me to the part of the PnC critical for startle (Meloni and Davis, 1999b).…”
Section: Discussionmentioning
confidence: 61%
“…Davis, 1984) and is mediated by a simple neural pathway in the brainstem consisting of cochlear root neurons (CRNs), neurons in the nucleus reticularis pontis caudalis (PnC), and motoneurons in the spinal cord (Lee et al, 1996). The amplitude of this short-latency response can be quantified easily and has been used extensively to study the neurocircuitry and neurochemistry involved in the modulation of reflex/motor behavior (cf.…”
Section: Abstract: Startle; Superior Colliculus; Bicuculline; Muscimmentioning
confidence: 99%